Antifungal properties of aqueous microalgal extracts. (June 2022) - Schmid, Benjamin; Coelho, Luísa; Schulze, Peter S.C.; Pereira, Hugo; Santos, Tamára; Maia, Inês B.; Reis, Mário; Varela, João
Abstract: Microalgae are considered a promising source of eco-friendly antifungal agents that can potentially reduce the usage of synthetic fungicides. Hence, properties of aqueous extracts from Nannochloropsis sp., Phaeodactylum tricornutum, Scenedesmus obliquus, Chlorella vulgaris and Spirulina sp. were investigated in vitro regarding their antagonistic activity towards the phytopathogenic fungi Sclerotium rolfsii, Rhizoctonia solani, Botrytis cinerea and Alternaria alternata . S. obliquus showed the highest antifungal activity of all microalgal strains against Sclerotium rolfsii, inhibiting growth up to 32.01 ± 4.82% . Nannochloropsis sp. mitigated Sclerotium rolfsii by up to 13.96 ± 5.26%, while P. tricornutum suppressed the mycelial growth of Sclerotium rolfsii and Rhizoctonia solani by up to 18.35 ± 3.45%. Moreover, P. tricornutum and S. obliquus inhibited Botrytis cinerea growth by up to 11.47 ± 2.06%. The obtained results indicate that microalgae with fungicidal activity could replace chemical agents in modern and sustainable agricultural food production. Graphical abstract: Unlabelled Image Highlights: Aqueous extracts of Phaeodactylum and Scenedesmus showed best antifungal properties. Scenedesmus obliquus inhibited Sclerotium rolfsii growth by up to 32%. Phaeodactylum tricornutum suppressed Rhizoctonia solani growth by up to 18.35%. Algal fungicides can reduce the usage of synthetic pesticides. Algal biomass might be used in plant disease management.